Synthesis of Nonsymmetric Iminophosphonamines by Kirsanov Condensation - Peganova, Tatyana A.; Kalsin, Alexander M. (Synthesis, 2020)
Despite the growing interest in iminophosphonamines R2P(NHR′)(NR′), nonsymmetric examples bearing different N,N′-substituents are quite rare and have been prepared exclusively by the Staudinger reaction. We report here the synthesis of a series of new iminophosphonamines Ph2P(NHR)(NR′) (R = Me, t-Bu, o-Tol; R′ = p-Tol, o-Tol, 2,6-Xyl, 2,6-Diip, p-Ts) showing that the Kirsanov condensation is a viable and simpler approach, although with some limitations. This method allows the synthesis to be accomplished in a one-pot manner via stepwise double amination of a trihalophosphorane and permits the introduction of at least one sterically bulky N-substituent. The second amination step is shown to be highly sensitive to: (a) the steric bulk of the amine, and (b) the acidity of the aminohalophosphonium intermediate.
Keywords: Kirsanov condensation; nonsymmetric iminophosphonamines; steric effects; aminohalophosphonium